Peningkatan Kemampuan Menulis Menggunakan Project Based Learning Dengan Media Cerpen Dalam Pembelajaran Drama Kelas VIII SMPN 3 Rejoso - Wahyu Agung Widodo; Sri Lestari; Sri Wahyuni (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research is a classroom action research (PTK) that aims to improve the writing skills of grade VIII-B students of SMPN 3 Rejoso through Project Based Learning with the help of short stories as a tool in improving students' writing skills. The research procedure uses two cycles, each cycle has stages of planning, implementing actions, observation, and reflection. The time for this research is carried out from March to April 2023. The subjects in this study were students of grade VIII-B SMPN 3 Rejoso totaling 29 students. This study used a quantitative descriptive research design. The results of this study show that in general, the Project Based Learning learning model with short story media has been effectively used in drama learning in the drama writing subchapter. Keywords: Project Based Learning, Short Story Media, Drama Writing